The Zionist ideas : visions for the Jewish homeland--then, now, tomorrow - Troy, Gil; Shcharansky, Anatoly (Lincoln : University of Nebraska Press, 2018)
"The most comprehensive Zionist collection ever published, The Zionist Ideas: Visions for the Jewish Homeland --Then, Now, Tomorrow builds on Arthur Hertzberg's classic The Zionist Idea, showcasing more than 170 visionaries and shedding light on the surprisingly diverse and shared visions for realizing Israel as a democratic Jewish state"--
Includes bibliographical references.
"Published by the University of Nebraska Press as a Jewish Publication Society book."
Description based on online resource; title from PDF title page (EBSCO, viewed March 6, 2018).
Master record variable field(s) change: 072
Keywords: Zionism -- History -- Sources; RELIGION / Judaism / History; SOCIAL SCIENCE / Jewish Studies; HISTORY / Middle East / Israel; Zionism; POLITICAL SCIENCE / Essays; POLITICAL SCIENCE / Government / General; POLITICAL SCIENCE / Government / National; POLITICAL SCIENCE / Reference; History; Sources; Electronic books